Absence of Interleukin-4 Determines Less Severe Pulmonary Paracoccidioidomycosis Associated with Impaired Th2 Response - Pina, Adriana (American Society for Microbiology, 2004)
Host resistance to paracoccidiodomycosis, the main deep mycosis in Latin America, is mainly due to cellular immunity and gamma interferon (IFN-γ) production. To assess the role of interleukin-4 (IL-4), a Th2-inducing cytokine, pulmonary paracoccidioidomycosis was studied in IL-4-deficient (IL-4(−/−)) and wild-type (WT) C57BL/6 mice at the innate and acquired phases of immune response. Forty-eight hours after infection, equivalent numbers of viable Paracoccidioides brasiliensis yeast cells were recovered from the lungs of IL-4(−/−) and WT mice intratracheally infected with one million fungal cells. Alveolar macrophages from infected IL-4(−/−) mice controlled in vitro fungal growth more efficiently than macrophages from WT mice and secreted higher levels of nitric oxide. Compared with WT mice, IL-4(−/−) animals presented increased levels of pulmonary IFN-γ and augmented polymorphonuclear leukocyte influx to the lungs. Decreased pulmonary fungal loads were characterized in deficient mice at week 2 postinfection, concomitant with diminished presence of IL-10. At week 8, lower numbers of yeasts were recovered from lungs and liver of IL-4(−/−) mice associated with increased production of IFN-γ but impaired synthesis of IL-5 and IL-10. However, a clear shift to a Th1 pattern was not characterized, since IL-4(−/−) mice did not alter delayed-type hypersensitivity anergy or IL-2 levels. In addition, IL-4 deficiency resulted in significantly reduced levels of pulmonary IL-12, granulocyte-macrophage colony-stimulating factor, IL-3, monocyte chemotactic protein 1, and specific antibody isotypes. In IL-4(−/−) mice, well-organized granulomas restraining fungal cells replaced the more extensive lesions containing high numbers of fungi and inflammatory leukocytes developed by IL-4-sufficient mice. These results clearly showed that genetically determined deficiency of IL-4 can exert a protective role in pulmonary paracoccidioidomycosis.